Military K-9 Unit: Christmas - Scott, Laura, 1961-; Hansen, Valerie (New York : Love Inspired Books, 2018)
When Captain Isaac Goddard saves Vanessa Gomez from a vicious attack, he discovers the feisty military nurse is the Red Rose Killers next target. With help from Vanessas guard Doberman, the former pilot makes it his mission to protect Vanessa and her young brother. But when the danger closes in, can he overcome the post-traumatic stress that haunts him and stop a ruthless killer?
"True large print"--Cover.
"Inspirational romantic suspense"--Spine.
Keywords: Nurses -- Fiction; Service dogs -- Fiction; Post-traumatic stress disorder -- Fiction; Man-woman relationships -- Fiction; Large type books; Romantic suspense fiction; Romance fiction